Multimodal Transportation in Urban Parcel Delivery Systems (2024)
Due to the negative impacts that last-mile delivery generate in the environment and people's wellbeing, it is important to rethink how urban parcel distribution networks currently work to make them eco-friendlier and more robust without compromising their efficiency. This thesis proposes a new setup for urban logistics networks, using not only roadways, but also inland waterways and different transportation modes such as barges, electric cargo bikes, and delivery vans. Multiple case studies using real data from delivery companies in three French cities are studied in some chapters of this manuscript to design and model the urban parcel delivery networks, treating them as two-echelon distribution systems.